Spanish crowdfunding as a new social tool to empowering the sustainability - Rubio Martín, Gracia (REVESCO. Revista de Estudios Cooperativos, 2020)
The objective of this document is to analyze the role of crowdfunding in Spain oriented to finance activities with positive impact: social and ecological. First, throughout a review of the theoretical framework, second, across an analysis about the situation of the sector in Spain resulting from a structured questionnaire, answered by the crowdfunding plataforms’ managers. The article analyzes the taxonomy of the sector in Spain, its evolution, as well as the profitability, risks and opportunities that it offers to entrepreneurs and investors. There is no doubt that Internet is playing a decisive role transforming the society in a new economic-decision agent that designs its own destiny. After the review, in line with the theoretical frame work, the article concludes that crowdfunding turns out to be a very useful tool to achieve growth based on sustainability. This phenomenon is changing the old paradigm of the investors, from an agent without scruples, to one other that is socially and emotionally responsible, being able to create a virtuous circle in which economic profitability and improvements on its environment are feed-back.